Evaporative Self‐Assembly of Gold Nanorods into Macroscopic 3D Plasmonic Superlattice Arrays. Issue 13 (29th January 2016) - Li, Penghui; Li, Yong; Zhou, Zhang‐Kai; Tang, Siying; Yu, Xue‐Feng; Xiao, Shu; Wu, Zhongzhen; Xiao, Quanlan; Zhao, Yuetao; Wang, Huaiyu; Chu, Paul K.
Abstract : Millimeter‐scale 3D superlattice arrays composed of dense, regular, and vertically aligned gold nanorods are fabricated by evaporative self‐assembly. The regular organization of the gold nanorods into a macroscopic superlattice enables the production of a plasmonic substrate with excellent sensitivity and reproducibility, as well as reliability in surface‐enhanced Raman scattering. The work bridges the gap between nanoscale materials and macroscopic applications.